Fenomena Milenial dan Syari’at Islam di Aceh - Vatta Arisva; Miftahul Jannah; Nahdia Asyifah (Jurnal Community, 2023)
A concert in Aceh which was held in an event entitled Seulawah Expo, attracted the attention of many parties. The reason is that many young people are mixed between men and women, although the organizing committee has given a fence of boundaries between men and women. This is the attraction of this research, because the incident occurred in Aceh, known as the Porch of Mecca. Therefore, it gives birth to the following research questions. First, what is the view of Acehnese millennials in understanding Islamic shari'a? Second, how does the moral perspective see the phenomena among Aceh's millennials? This qualitative research uses a descriptive analysis method of Islamic sharia phenomena that occurred in Aceh. While the data source is in the form of secondary data, so as to produce the following conclusions: First, the understanding of Islamic law among millennials can be shared with three forms of groups, some still understand, some do not understand and some do not understand indifferent attitudes. It is also based on maturity or maturity and social control of the values that live in society. Second, that technological developments on the influence of culture and values among millennials are very worrying. Where based on the phenomenon found, it has injured islamic sharia values in Aceh, which has caused moral degradation of millennials with the argument of freedom.